2021
DOI: 10.1177/20501684211033391
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Pandemic: The Urgent Dental Hub experience from a primary care perspective

Abstract: In response to the nationwide lockdown on 23 March 2020 in the UK, urgent dental hubs (UDHs) were established in the community to provide emergency dental care. Consecutive referrals to a primary care UDH were prospectively analysed over a one-month period, from 18 May 2020 to 18 June 2020. Of 400 referrals received, the most common were in relation to pain (87%). In 63% neither a radiograph nor photograph was provided with the referral. Seventy percent of patients were telephone triaged within 24 hours of r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…23,24 Analysis of care provided for patients before referral into UDC hubs found that half of their patients had received a course of antibiotics before their onward referral into a UDC for treatment, with many appearing to be an inappropriate use of antibiotics. 25,26 No differences were apparent in the survey results between the NHS regions, although the relatively low number of participants per region made statistical comparison inappropriate. Future preparedness planners should include evidence from around the UK about the best way to deliver UCDs quickly during a pandemic in areas with and without dental hospitals.…”
Section: Discussionmentioning
confidence: 99%
“…23,24 Analysis of care provided for patients before referral into UDC hubs found that half of their patients had received a course of antibiotics before their onward referral into a UDC for treatment, with many appearing to be an inappropriate use of antibiotics. 25,26 No differences were apparent in the survey results between the NHS regions, although the relatively low number of participants per region made statistical comparison inappropriate. Future preparedness planners should include evidence from around the UK about the best way to deliver UCDs quickly during a pandemic in areas with and without dental hospitals.…”
Section: Discussionmentioning
confidence: 99%